Temporal trend of age at menarche in Korean females born between 1927 and 2004: a population-based study - Lee, Da Hye; Kim, Jaehyun; Kim, Hwa Young (Frontiers in Endocrinology, 2024)
The age at menarche has decreased worldwide. Previous studies on Korean adolescents have reported a downward trend in age at menarche. This study aimed to investigate the current trends in age at menarche among Korean adolescents using nationally representative data.The study used data from the Korea National Health and Nutrition Examination Survey 2007-2021. A total of 50,730 females born between 1927 and 2004 with information on age at menarche were included. The trend in age at menarche was analyzed according to 15 birth-year groups (with 5-year intervals) using quantile regression analysis.The mean age at menarche decreased from 16.92 ± 0.06 years for females born before 1935 to 12.45 ± 0.04 years for females born between 2000 and 2004 (p <.001). According to the percentile group of age at menarche, mean menarche age decreased by -0.071 years per year (95% confidence interval [CI], -0.072 to -0.070) in total, -0.050 years per year (95% CI, -0.052 to -0.048) in the 3rd percentile group, -0.088 years per year (95% CI, -0.091 to -0.085) in the 97th percentile group (p <.001 for all). A decreasing trend of age at menarche was more prominent in the obesity group (-0.080 years per year, 95% CI, -0.082 to -0.078) compared to the non-obesity group (-0.069 years per year, 95% CI, -0.071 to -0.068) (p <.001 for both).Ongoing downward trend in age at menarche was observed in Korean females born until 2004, decreasing by 0.71 years per decade. The downward trend was faster in individuals with a higher percentile of age at menarche and in those with obesity.